2013
DOI: 10.1136/jramc-2013-000188
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided botulinum toxin injection to treat a parotid fistula following gunshot injury

Abstract: Parotid fistula is a rare but very distressing sequelum of post-operative or traumatic injuries. The management of these injuries has been reported in the literature previously and techniques employed include pressure dressings, surgery and more recently botulinum toxin A (BTA) injections. We present a patient who developed a parotid fistula as a late complication of an extensive gunshot injury to the face with subsequent successful management with ultrasound-guided intraglandular injections of BTA. This case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…[5] Sialography can also be used to detect damage to the Stenson's duct. In a study by Gok et al, [6] it was reported that intraparenchymal Botulinum Toxin A injection was effective and more comfortable for the patient with salivary fistula. In cases where the facial nerve is damaged, early exploration and end-to-end anastomosis should be performed immediately after the patient has stabilized.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Sialography can also be used to detect damage to the Stenson's duct. In a study by Gok et al, [6] it was reported that intraparenchymal Botulinum Toxin A injection was effective and more comfortable for the patient with salivary fistula. In cases where the facial nerve is damaged, early exploration and end-to-end anastomosis should be performed immediately after the patient has stabilized.…”
Section: Discussionmentioning
confidence: 99%